Development of Web and Cloud Computing-Based Chatbot Services for Enhancing Academic Services at Panca Budi University - Lubis, Akhyar; Sumartono, Isnar (International Conference on Sciences Development and Technology, 2022)
This research aims to develop web and cloud-computing-based chatbot services that can enhance academic services at Panca Budi University. The study highlights the importance of information and communication technology in education and the challenges universities face, such as less interactive academic services and long waiting times. The proposed solution is the development of a web and cloud-computing-based chatbot that can provide quick and accurate responses to student inquiries. Cloud computing in chatbot management also offers additional benefits, such as efficiency and continuous service availability. The research methodology employed a waterfall-based development approach, outlining the stages of chatbot development. Implementing the web-based chatbot utilized Amazon Lex services and integration with other AWS services. Testing results showed that the chatbot improved accessibility to academic information, reduced waiting times, and enhanced the quality of student interactions. The adoption of AWS cloud computing services enabled the chatbot to be accessed online 24/7. The successful development of the chatbot will help meet student needs and enhance academic services at Panca Budi University